PhU as a means of characterization of a person’s appearance (based on the material of the English language) - Balyasnikova , Marina (The Lingua Spectrum, 2025)
The article is dedicated to the analysis of English phraseological units characterizing a person’s appearance. Each phraseological unit (PhU) is characterized by a specific set of units of meaning, minimal semantic components – semes, integral and differential. If integral semes are the most general and serve as the basis for combining PhU into certain phraseo-semantic groups and subgroups, the differential semes are additional semantic features and reflect secondary properties and characteristics of the designated phenomenon. The significative-denotative component of the phraseological meaning reflects the complexity of the concept expressed by the phraseological unit, and may include both integral and differential semes. The evaluative component, i.e. the approving or disapproving appraisal in the meaning of the phraseological unit, is the main in the connotative meaning of PhU due to its sociolinguistic nature. The negative, positive and neutral components of phraseological meaning are distinguished, and this distinction is based on condemnation, approval or lack of approval or condemnation as a statement of a socially established evaluation of a phenomenon. The evaluative and emotional components are closely connected within the semantics of a PhU. The functional and stylistic component of the connotation indicates that the phraseological unit belongs to a particular style of speech, its prevalence and usage.